Strategies for the application of the Waterlow scale to the person with spinal cord injury: experience report - Rita Mônica Borges Studart; Islene Victor Barbosa; Francisca Elisângela Teixeira Lima; Zuila Maria de Figueredo Carvalho (Rev Rene)
A person with spinal cord injury, during hospitalization, has as complication the ulcers of pressure. The objective of this work was to report the experience of using the Waterlow scale in people with spinal cord injury. It is a report of experience with the implementation of the Waterlow scale in 60 hospitalized patients with spinal cord injury in a tertiary public hospital in Fortaleza-CE. The results showed that the use of the Waterlow Scale with the person with spinal cord injury requires strategies to enable implementation. For so, it was designed a standard operating protocol, which aimed to standardize the physical examination. This prediction tool showed that people with spinal cord injury are very high risk of developing pressure ulcers, and prevention measures should be taken immediately at the beginning of hospitalization. It was found that, despite the inability to weigh and measure the patient with spinal cord injury, it was possible to use the Waterlow scale with such patients.